Pemenuhan Hak Pekerja Host Live Streaming Tiktok Shop Dalam Economy Gig - Wulandari, Fitria Amesti; Alifah, Andi Sitti Ainy Nur (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The labor market in Indonesia is facing an increase in its flexibility, which consequently results in more flexible jobs. Flexibility of jobs is actually one of the characteristics of jobs available in the gig economy, whose labours are known as gig workers. The flexible characteristics of gig jobs leads to workers depending their lives by working as the said gig workers, one of which is by becoming a TikTok Shop live streaming host. However, in its development, the flexibility that should be one of the advantages of gig workers actually makes TikTok Shop live streaming hosts vulnerable to exploitation and violations of their rights. Departing from these phenomenon and concerns, this study will examine in more depth what are the categorisations of gig workers, how is the relationship between TikTok Shop live streaming hosts with companies and agencies, and how to fulfill the rights of TikTok Shop live streaming host in the gig economy. With that, the method in this study uses empirical legal research with a statutory regulatory approach and a conceptual approach. The data used in this study are primary data collected through interviews (in-depth interviews) and secondary data through literature studies. The results of this study show; (i) TikTok Shop live streaming hosts are categorised as gig workers; (ii) In practice, TikTok Shop live streaming hosts have legal relationships with companies and agencies, both of which are included in employment relationships; and (iii) The implementation of workers' rights for TikTok Shop live streaming hosts in employment relationships is not yet optimal.Keywords: Economy Gig, Workers' Rights, TikTok Shop Live Streaming Hosts, Gig Workers AbstrakPasar tenaga kerja di Indonesia telah mengalami peningkatan dalam fleksibilitasnya yang menghadirkan beberapa jenis pekerjaan yang lebih fleksibel. Fleksibilitas dalam pekerjaan tersebut sejatinya menjadi salah satu karakteristik dari pekerjaan dalam economy gig atau dikenal sebagai gig worker. Karakteristik gig worker yang fleksibel kemudian membuat para pekerja menggantungkan hidupnya dengan bekerja sebagai gig worker, salah satunya menjadi host live streaming TikTok Shop. Namun, dalam perkembangannya, fleksibilitas yang seharusnya dapat menjadi salah satu kelebihan dari gig worker tersebut justru membuat host live streaming TikTok Shop rentan terhadap eksploitasi dan pelanggaran haknya. Berangkat dari fenomena dan kekhawatiran tersebut penelitian ini akan mengkaji secara lebih mendalam terkait apa saja kategorisasi gig worker, bagaimana hubungan antara host live streaming TikTok Shop dengan perusahaan dan agensi, serta bagaimana pemenuhan hak pekerja host live streaming TikTok Shop dalam economy gig. Metode dalam penelitian ini menggunakan penelitian yuridis empiris dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Data yang digunakan adalah data primer yang dikumpulkan melalui wawancara (in depth interview) serta data sekunder melalui studi kepustakaan. Hasil dari penelitian ini menunjukkan; (i) Host live streaming TikTok Shop terkategorisasikan sebagai gig worker; (ii) Dalam praktiknya para host live streaming TikTok Shop mengadakan hubungan hukum dengan perusahaan dan agensi, yang mana keduanya termasuk ke dalam hubungan kerja; dan (iii) Implementasi hak pekerja terhadap host live streaming TikTok Shop dalam hubungan kerja belum optimal.Kata Kunci: Economy Gig, Hak Pekerja, Host Live Streaming TikTok Shop, Pekerja Gig